2021
DOI: 10.2147/jbm.s312140
|View full text |Cite
|
Sign up to set email alerts
|

Leukapheresis Does Not Improve Early Survival Outcome of Acute Myeloid Leukemia with Leukostasis Patients – A Dual-Center Retrospective Cohort Study

Abstract: Introduction:Leukostasis is a medical emergency with high mortality which often occurs in acute myeloid leukemia patients with hyperleukocytosis. One of the therapies that can be used for leukostasis in acute myeloid leukemia is leukapheresis. However, whether leukapheresis can provide better survival benefit when compared with patients not receiving leukapheresis is still unclear. Hence, we aimed to evaluate the effect of chemotherapy plus leukapheresis combination versus chemotherapy only on 28-day survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…However, the use of leukocytapheresis in the absence of additional cytoreductive agents may provide only very temporary, if any, reduction in circulating WBC. Several retrospective studies have been recently published evaluating the use of leukocytapheresis; none demonstrate definitive benefit on survival (Rinaldi, 2021;Gelen 2022).…”
Section: Rationale For Therapeutic Apheresismentioning
confidence: 99%
“…However, the use of leukocytapheresis in the absence of additional cytoreductive agents may provide only very temporary, if any, reduction in circulating WBC. Several retrospective studies have been recently published evaluating the use of leukocytapheresis; none demonstrate definitive benefit on survival (Rinaldi, 2021;Gelen 2022).…”
Section: Rationale For Therapeutic Apheresismentioning
confidence: 99%
“…It may indicate the likelihood of extramedullary dissemination of blats which in turn increases the risk of treatment failure and disease recurrence. 37 We also observed that normal ESR at diagnosis was associated with 10% higher mortality, though the estimate had a wide CI which makes the assumption less certain. High ESR is a non-specific sign of inflammation that is commonly observed in childhood leukemia.…”
Section: Discussionmentioning
confidence: 74%
“…We reported for the first time that hepatomegaly is associated with about five times higher risk of mortality in children with ALL. It may indicate the likelihood of extramedullary dissemination of blats which in turn increases the risk of treatment failure and disease recurrence 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there is no definitive evidence demonstrating a mortality benefit for leukapheresis in patients with hyperleukocytosis and hence it is not a part of the treatment algorithm ( 14 , 16 ). Leukapheresis may be considered in patients with AML with ongoing leukostasis as an adjunct to initiation of chemotherapy ( 11 , 16 18 ) or patients with CML with evidence of priapism, hearing loss, visual changes, or pulmonary infiltrates ( 19 ). Initiation of leukapheresis is often time consuming as it requires placement of specialized central lines and mobilization of multiple services.…”
Section: Hyperleukocytosis Pathwaymentioning
confidence: 99%